2022
DOI: 10.1289/ehp9688
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 and Serum Metabolome and Insulin Resistance, Potential Mediation by the Gut Microbiome: A Population-Based Panel Study of Older Adults in China

Abstract: Background: Insulin resistance (IR) affects the development of type 2 diabetes mellitus (T2DM), which is also influenced by accumulated fine particle air pollution [particulate matter (PM) with aerodynamic diameter of ( )] exposure. Previous experimental and epidemiological studies have proposed several potential mechanisms by which contributes to IR/T2DM, including inflammation imbalance, oxidative stress, and endothelial dysfunction. Recent evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(35 citation statements)
references
References 77 publications
0
35
0
Order By: Relevance
“…Finally, 12 articles were considered eligible to be included in the systematic review, but 2 articles were excluded for missing data. A total of 10 articles were used for the data extraction [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The PRISMA flow diagram in Figure 1 illustrates the search results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 12 articles were considered eligible to be included in the systematic review, but 2 articles were excluded for missing data. A total of 10 articles were used for the data extraction [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The PRISMA flow diagram in Figure 1 illustrates the search results.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies (nine cross-sectional and one cohort study) were published from 2018 to 2022 [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] ( Table 2 ). Among the ten studies, two of them were conducted in America [ 39 , 45 ], seven in China [ 36 , 37 , 38 , 40 , 41 , 42 , 43 ], and one in Europe (Finland) [ 44 ], and the sample size was very variable, ranging from 21 to 6627 subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota dysbiosis and insulin resistance might be one of possible mechanisms. Both in vivo and prospective studies have indicated that chronic exposure to PM2.5 caused dysbiosis of the gut microbiota and may subsequently contribute to the development of abnormal glucose metabolism and insulin resistance [ 55 , 56 , 57 , 58 ]. Previous studies presented that gut microbiota affected bioprocessing of bile acids and production of pro-inflammatory intermediate metabolites resulting in hepatic disorders [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of lipid and fatty acid pathways is most likely to be used as sources of energy that promotes BC cell growth in addition to pathogenesis. The previous investigation on PM 2.5 and metabolism revealed that the impact of PM 2.5 on the genera of the gut microbiota could partially mediate the relationship between PM 2.5 and sphingolipid metabolism ( 48 ). In addition, the gut microbiota can affect host health by plasma metabolites ( 49 ).…”
Section: Discussionmentioning
confidence: 99%